2019
DOI: 10.1177/1524838019889359
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Educational Intervention in Improving Primary Health-Care Service Providers’ Knowledge, Identification, and Management of Elder Abuse and Neglect: A Systematic Review

Abstract: Elder abuse and neglect (EAN) occurrence is expected to increase in many countries due to rapidly aging populations, yet it is still unrecognized and underreported. Gaps were identified in the knowledge and skills to intervene EAN among health-care service providers. It is still unclear whether educating health-care service providers on EAN improve the identification and management of EAN cases. A systematic review was conducted on the effectiveness of educational intervention designed to improve primary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
1
27
0
2
Order By: Relevance
“…When health care professionals' attitudes and knowledge about elder abuse are studied, results are often reported without the measurements that were based on validated questionnaires [15]. Similarly, many training programs do not include validated instruments to measure the effect of the program [26,27]. Evaluations of interventions are also often limited to knowledge about elder abuse and satisfaction with training on the topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When health care professionals' attitudes and knowledge about elder abuse are studied, results are often reported without the measurements that were based on validated questionnaires [15]. Similarly, many training programs do not include validated instruments to measure the effect of the program [26,27]. Evaluations of interventions are also often limited to knowledge about elder abuse and satisfaction with training on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of interventions are also often limited to knowledge about elder abuse and satisfaction with training on the topic. Changes in attitudes and practices are typically not considered [26].…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing these 37 articles, 25 were excluded (not a systematic review/meta-analysis, abuse, and neglect not examined, and not a peer-reviewed journal article). This resulted in 12 full-text articles reporting on 11 unique reviews, which were included in this review (Alt et al, 2011;Ayalon et al, 2016;Baker et al, 2016Baker et al, , 2017Day et al, 2017;Fearing et al, 2017;Hirst et al, 2016;Mohd Mydin et al, 2019;Moore & Browne, 2017;Ploeg et al, 2009;Rosen, Elman et al, 2019;Wang et al, 2015).…”
Section: Search Strategy and Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…Further, abuse among older adults is quite prevalent in institutional settings and often leads to serious physical injuries and long-term psychological consequences (World Health Organization, 2018). As populations continue to age worldwide over the next several decades, abuse and neglect among older adults are predicted to increase exponentially (Mohd Mydin et al, 2019;World Health Organization, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed that educational intervention improved the knowledge, attitude, and practice of primary health care providers (Mohd Mydin et al, 2021). However, most of the studies in the review evaluated a one-time educational intervention and none measured the long-term sustainability of the knowledge and change of practice.…”
Section: Elder Abuse and Neglect Education Interventionmentioning
confidence: 99%